(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
This paper mainly focuses on dealing with the problems faced by the deaf and the dumb community in India in using the future technologies mainly personal assistance tools, may it be Alexa home or Amazon echo. We propose to make use of the standard Indian sign language as well as the sign language dictionary to create a manual entries of sign languages to a user interface which makes use of these sign language dictionary to convert the signs shown by a speech or noise impaired person by taking inputs from digital cameras or the laptop cameras in order to convert them into speech and made useful to the personal assistance tools that just takes audio voice as inputs. It is built by using machine learning tools which includes a TensorFlow library package. The whole project is user made to be user friendly to the community that will make use of it the most as well as easily understandable by the personal assistance tools in use worldwide. The project promises to ease the work of a speech disabled individual may it be through easy conversion of sign languages for a video call which helps the receiver get written transcripts of the signs displayed by the individual on the other end. However the main purpose of the project is with the purpose of helping such individuals make use of personal assistance tools which poses as an essential tool in the future to come.